Analisis Keuntungan Pemasaran Bunga Mawar Potong (Rosa hybrida L.) Di Surabaya - Dinda Ayu Sofiana; Koesriwulandari Koesriwulandari; Endang Siswati (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2022)
The purpose of this study is to find out marketing costs, analyze profits in marketing and find out the factors that influence the marketing advantages of cut roses at the Kayoon Flower Market Surabaya. The research method used is simple random sampling. The respondents in this study were 30 cut rose vendors. The data analysis method uses multiple linear regression analysis. Based on the results of multiple linear regression, the marketing profit model of cut roses at the Kayoon Flower Market Surabaya is as follows: Y= 2956323,939 – 2,973X1 + 1,067X2 + 6,892X3 – 0.475X4 + e. Based on F – statistics of 4,346 with a significance of 0.008%, it can be interpreted that simultaneously all marketing activities carried out include stand rental costs, levy costs, transportation costs and labor costs have a significant effect on marketing profits cut roses at Kayoon Flower Market Surabaya. Partially marketing activities that have a significant effect on marketing profits are stand rental costs and transportation costs.Keywords: Cut Roses, Marketing Profits, Multiple Linear Regression